Aplicación web para el intercambio de libros (canjeando) (2024)
This document presents the “Canjeando” project which was executed for the specialization in software engineering at the Antonio Nariño University. This project's main objective is to provide a space where readers can have contact with other readers interested in exchanging books. that they are in perfect condition through a web application designed for this purpose. For the development of this project, the scrumban methodology was used to review tasks and progress. The backend of the application was built with the Java programming language together with the spring boot framework, the angular framework was used to build the frontend and a MariaDB database was used to store the information from the books.